(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Artists and litterateurs are often inspired by events of national significance. The carnage of Partition and its aftereffects had left its lasting imprints in the inner psyche of prominent writers in India and Pakistan. Bapsi Sidhwa’s novel Ice-Candy-Man is based on such backdrop of the Partition of the Indian subcontinent and its horrible aftereffects. The novel throws sufficient light on the riots before and after the Partition.